ANALISIS PENGARUH AKUNTANSI BERBASIS SAK EMKM DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN PADA KUALITAS LAPORAN KEUANGAN UMKM (Studi Kasus pada UMKM Sektor Hasil Tani dan Ternak Kabupaten Pasuruan) - Alfian Shofi Alhamzah; Afifudin Afifudin; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The financial reports presented by MSMEs are still not good. MSME actors are still recording only cash income and disbursements. The purpose of this study was to determine the effect of SAK EMKM-based accounting and training in financial reporting on the quality of MSME financial reports. The data used in this study are primary data. In 2016 the number of MSMEs registered in cooperatives and SMEs in Pasuruan was 248.802 and in the following year it increased to 255.533, So it can be concluded that there were an additional 5550 business units in just one year. To obtain research samples, by conducting case study research on the agricultural and livestock sector in Pasuruan Regency. The sampling technique was carried out by using a questionnaire method which was distributed to SME entrepreneurs in the agricultural and livestock sector. The results obtained by using multiple linear regression test Y = 24.487 + 0.030X1 + 0.002X2 + ϵ, and the test of this study also used the t-test. The results of the t-test indicate that EMKM-based SAK accounting and financial reporting training have a positive effect on the quality of financial reports.Keywords: Accounting, SAK EMKM, training in preparing financial reports and the quality of financial reports